2014
DOI: 10.1177/1715163514530098
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists Connect and CARE

Abstract: The landscape of community pharmacy practice is changing rapidly across Canada. New pharmacy service frameworks are being implemented across the country, giving community pharmacists the ability to prescribe, inject medications and provide routine medication reviews. 1 With the implementation of new service frameworks, increased emphasis on working within a patientcentred care model and the intensifying need for accessible health care services, community pharmacists are currently facing pressure to shift from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The need for health education providing information about the patients’ conditions as well as appropriate management was also expressed by CRD patients themselves in previous studies [ 29 , 41 , 42 ]. Furthermore, interventions involving pharmacists to encourage customers to seek appropriate medical attention if their symptoms persists could help to improve the linkages between patients and the health system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for health education providing information about the patients’ conditions as well as appropriate management was also expressed by CRD patients themselves in previous studies [ 29 , 41 , 42 ]. Furthermore, interventions involving pharmacists to encourage customers to seek appropriate medical attention if their symptoms persists could help to improve the linkages between patients and the health system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists know their patients personally because of their frequent interaction, which develops patients' con dence in their pharmacists (51). Along with education on medical topics, the pharmacists view themselves as healthcare professionals who also provide empathy and reassurance (52). Therefore, the pharmacists' advice and reassurance will make an impact on the patients' decision to vaccinate, thus contributing to vaccine acceptance (53).…”
Section: Discussionmentioning
confidence: 99%
“…34 Similar to other studies, we found that patients deeply value the relationship they have with their primary care physician but did find they may not see value in a comparable relationship with their pharmacist. 35 Furthermore, it was clear that participants were aware that their pharmacist and physician did not work together as a team. Thus, future EHR design needs to consider how to convey the role each HCP has played in a patient decision to start or modify treatment.…”
Section: Patient Portals and Personal Health Records Have Helped Patients See What Informationmentioning
confidence: 99%